2019
DOI: 10.3389/fonc.2019.00433
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation Between G1 and G2/G3 Phyllodes Tumors of Breast Using Mammography and Mammographic Texture Analysis

Abstract: Purpose: To determine the potential of mammography (MG) and mammographic texture analysis in differentiation between Grade 1 (G1) and Grade 2/ Grade 3 (G2/G3) phyllodes tumors (PTs) of breast. Materials and methods: A total of 80 female patients with histologically proven PTs were included in this study. 45 subjects who underwent pretreatment MG from 2010 to 2017 were retrospectively analyzed, including 14 PTs G1 and 31 PTs G2/G3. Tumor size, shape, margin, density, homogenei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
4
14
0
Order By: Relevance
“…The results indicated that the diagnostic performance of the TA model or the combination model was greater than that achieved with image-based analysis alone (AUC: 0.894 vs 0.886 vs 0.687), even though there was no difference between the TA model and the combination model. Therefore, compared with conventional imaging findings based on human visual analysis, TA or combined with imaging findings has the potential in improving the differential diagnosis ability between BPTs and BMPTs, which is consistent with the result of a previous study by Cui et al (31), who found that combining mammography findings and texture features can provide optimal predictions in the classification of PTs in mammography.…”
Section: Discussionsupporting
confidence: 87%
“…The results indicated that the diagnostic performance of the TA model or the combination model was greater than that achieved with image-based analysis alone (AUC: 0.894 vs 0.886 vs 0.687), even though there was no difference between the TA model and the combination model. Therefore, compared with conventional imaging findings based on human visual analysis, TA or combined with imaging findings has the potential in improving the differential diagnosis ability between BPTs and BMPTs, which is consistent with the result of a previous study by Cui et al (31), who found that combining mammography findings and texture features can provide optimal predictions in the classification of PTs in mammography.…”
Section: Discussionsupporting
confidence: 87%
“…They concluded that the texture data obtained from MG images of PTs allowed identification of grade 1 PTs from grades 2 and 3. In addition, the combination of using both MG and texture findings increased both the sensitivity and specificity of the diagnoses [1].…”
Section: Discussionmentioning
confidence: 99%
“…Ein unabhängiger maschineller Lernansatz, MATLAB R2020a (Math Works, Natick, Massachu-Introduction Phyllodes tumors (PTs) are uncommon fibroepithelial breast lesions. Less than 1 % of breast lesions and 2-3 % of all fibroepithelial lesions are diagnosed as PTs [1]. They are classified as three different forms: benign (BPT), borderline (BoPT), and malignant phyllodes tumors (MPT) with a grading system accepted by the World Health Organization [2].…”
Section: Zusammenfassungmentioning
confidence: 99%
“…In the recent years, radiomics increasingly draws attention and has demonstrated that it may be a tool that can obtain high-fidelity target information to comprehensively evaluate lesions, especially the texture features in the image that are not recognized by the naked eye and reveal the inherent heterogeneity of the tissue, reflecting the subtle differences between different tissues. Radiomics can be combined with the imaging appearance to further improve the differential diagnosis ability of the lesion ( 30 , 31 ). The AK, an imaging analytic software used in this study, has been used in many research reports ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%